myocardial reinfarction - case report - Mirković, Olja; Vukicevic, Verica; Radulovic, Marija (Halo 194 Scientific Journal of Emergency Medicine, 2025)
Introduction: According to the Fourth Universal Definition of Myocardial Infarction (MI), the term ″reinfarction″ is clinically used for MI occurring within 28 days of an incident or recurrent MI. It is characterized by the recurrence of anginal pain, an increase in cardiospecific enzymes and changes in the electrocardiogram. Aim: To point out the importance of early recognition and prehospital diagnosis of myocardial reinfarction that occurred shortly after the first MI, with implications for a positive patient outcome. Case report: A 64-year-old female called 194 because of chest pain accompanied by vomiting. Discharged two days earlier after hospitalization for anterior wall MI. Changes in the ST segment are observed on the ECG recording, which indicate an MI anterolateral localization. Appropriate therapy, he was transported to the angio room for further diagnosis and treatment. Conclusion: Fast and timely diagnosis of reinfarction plays a key role in the further treatment of the patient.